2015
DOI: 10.1016/j.visres.2014.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Perception of the material properties of wood based on vision, audition, and touch

Abstract: Most research on the multimodal perception of material properties has investigated the perception of material properties of two modalities such as vision-touch, vision-audition, audition-touch, and vision-action. Here, we investigated whether the same affective classifications of materials can be found in three different modalities of vision, audition, and touch, using wood as the target object. Fifty participants took part in an experiment involving the three modalities of vision, audition, and touch, in isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
99
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(104 citation statements)
references
References 34 publications
4
99
1
Order By: Relevance
“…In order to effectively design surface textures of products, it is crucial to understand the causal relationships among these different types of texture-related experiences. Especially because emotional and personal experiences significantly influence the value of a product, many studies have investigated experiences of pleasantness, comfort, and preference for product design purposes [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In order to effectively design surface textures of products, it is crucial to understand the causal relationships among these different types of texture-related experiences. Especially because emotional and personal experiences significantly influence the value of a product, many studies have investigated experiences of pleasantness, comfort, and preference for product design purposes [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Users recognise materials not only by assigning them to a specific category but also by estimating their quality, which sometime can be highly subjective and is detached from the objective utilities of the material (Fleming et al, 2013). For instance, dark, clear and glossy wood is evaluated as expensive, sophisticated, rare and interesting (Fujisaki et al, 2015), whereas a radial section of softwood evokes mellow, pleasing and natural feelings (Song & Zhao, 2011). In her research Karana found that when users appraise a material, typically there is a link between use and associative descriptions, and manufacturing process descriptions and sensorial descriptions.…”
Section: Materials Experiencementioning
confidence: 99%
“…According to previous reports, different materials could cause different warm/cold feelings to human subjects, even though they are at the same temperatures (Fenko et al 2010;Fujisaki et al 2015). Consequently, it was important to investigate the effects of different materials on the warm/cold feelings of human subjects touching heated and unheated heating floors.…”
Section: Warm/cold Feelings Of Human Subjectsmentioning
confidence: 99%